Multi sensor setup for high precision 3MA measurements of samples with uneven surfaces - Becker, Tim; Harms, Arnold; Merklein, Marion; Seewig, Jörg (Production Engineering, 2025)
Nondestructive testing (NDT) of materials plays a central role in quality assurance and condition monitoring of industrial manufacturing processes. As the level of automation increases, so does the demand for inline-capable testing methods that can be seamlessly integrated into process chains. This article examines a process chain for the production of bicycle chainrings as an application example, which combines resource-efficient orbital forming with a subsequent milling process. The near-net-shape preforming not only reduces machining effort but also influences the mechanical properties of the semi-finished product, particularly through work hardening and embedded residual stresses. These locally varying properties pose a challenge for subsequent processing and require precise characterization. For inline-capable determination of mechanical state variables such as hardness or residual stresses, the 3MA measurement technology (Micromagnetic multi-parametric microstructure and stress analysis) is used. It is an electromagnetic testing method for nondestructive determination of magnetic parameters in near-surface component areas. A key challenge is ensuring controlled measurement conditions, especially maintaining a constant distance between the probe and the sample (lift-off). Varying distances lead to systematic measurement errors. This work presents a measurement setup that enables adaptive, lift-off controlled measurements based on a laser triangulation sensor in combination with a coordinate measuring machine (CMM). This allows the lift-off to be actively controlled and kept constant. The solution is validated using orbitally formed chainring blanks. Comparative measurements with and without lift-off control demonstrate a significant improvement in measurement results. The article also discusses the mechanical design for mounting the sensors in the CMM and approaches for further optimization of the setup, including closed-loop control and collision protectio
Keywords: 3MA; Nondestructive testing; Sheet bulk metal forming; Orbital forming; Micromagnetics